Complete revascularization for patients with multivessel coronary artery disease and ST-segment elevation myocardial infarction after the COMPLETE trial: a meta-analysis of randomized controlled trial. (25th November 2020) - Bajraktari, G; Bytyci, I; Henein, M.Y; Alfonso, F; Ahmed, A; Jashari, H; Bhatt, D.L
Abstract: Background: The recently published COMPLETE trial has demonstrated that patients with ST-segment elevation myocardial infarction (STEMI) and multivessel coronary artery disease (MVD), who underwent successful percutaneous coronary intervention (PCI) of both culprit and non-culprit (vs. culprit-only) lesion had a reduced risk of major adverse cardiac events (MACE: cardiovascular mortality, myocardial infarction, or ischemia-driven revascularization), but not of cardiovascular or total mortality. Aim: To assess the efficacy of complete revascularization for cardiovascular or total mortality reduction by meta-analysis of all available randomized controlled trials (RCTs) including the COMPLETE trial. Methods: PubMed, MEDLINE, Embase, Scopus, Google Scholar, CENTRAL and ClinicalTrials.gov databases search identified 10 RCTs of 7033 patients with STEMI and MVD which compared complete (n=3420) vs. only culprit lesion (n=3613) PCI for a median 28.7 months follow-up. Random effect risk ratios were used for efficacy and safety outcomes. Results: Complete revascularization reduced the risk of MACE (10.4% vs. 16.6%; RR=0.59, 95% CI: 0.47 to 0.74, p<0.0001), CV mortality (2.87% vs. 3.72%; RR=0.73, 95% CI: 0.56 to 0.95, p=0.02), reinfarction (5.1% vs. 7.1%; RR=0.67, 95% CI: 0.52 to 0.86, p=0.002), urgent revascularization (7.92% vs. 17.4%; RR=0.47, 95% CI: 0.30 to 0.73, p<0.001), and CV hospitalization (8.68% vs. 11.4%; RR=0.65, 95% CI: 0.44to 0.96, p=0.03) compared with culprit only revascularization. All-cause mortality, stroke, major bleeding events, or contrast induced nephropathy were not affected by the revascularization strategy. Conclusion: The findings of this meta-analysis suggest that in patients with STEMI and MVD, complete revascularization is superior to culprit-only PCI in reducing the risk of MACE outcomes, including cardiovascular mortality, without increasing the risk of adverse safety outcomes. Funding Acknowledgement: Type of funding source: None